Role of the variable solar wind in the dynamics of small-scale magnetosheath structures - Rakhmanova, Liudmila; Riazantseva, Maria; Zastenker, Georgy; Yermolaev, Yuri (Frontiers in Astronomy and Space Sciences, 2023)
Varying solar wind plays a crucial role in the processes inside the magnetosphere. Statistical studies generally reveal the geoeffectiveness of solar wind streams of different origins and types, characterized by various parameters such as dynamic pressure and magnetic field orientation. However, the predictions of the space weather are still not completely reliable. Small-scale structures (observed as high-amplitude variations with frequencies above 0.01 Hz) involved in the turbulent flow of the solar wind and in the magnetosheath may contribute to the models’ inaccuracies. Spacecraft measurements obtained during last 2 decades provide a great amount of new information about small-scale plasma processes in near-Earth space. However, the influence of solar wind on the dynamics of the small-scale structures in the magnetosheath has been rarely addressed. The present review summarizes experimental studies on this influence including features of turbulence around ion scales. The study aims to give a general picture of the problem and underline the gaps in current understanding of the role of the dynamics of the small-scale structures and turbulence in the solar–terrestrial relations.